Screening of Glycosmis pentaphylla for Cytotoxic and Repellent Potentials agains Artemia salina Nauplii and Tribolium castaneum (Herbst) Adults (Journal of Life and Earth Science, 2011)
Chloroform extracts of the leaf, stem bark, stem wood and roots of Glycosmis pentaphylla (Retz.) were tested against the brine shrimp, Artemia salina nauplii for cytotoxic activity in which the dose-mortality assay revealed LC50 values of 28.579, 28.659, 57.213 and 84.111 ppm respectively, for the plant parts efficacy of which could be arranged in the order of leaf > stem bark > stem wood > root. The same extracts were tested for repellency against Tribolium castaneum (Herbst) adults where the root bark and root wood were separately extracted and used. The F values of the arcsin transformed data were 60.983, 14.177, 19.437, 15.429 and 1.082 respectively for the leaf, stem bark, stem wood, root bark and root wood extracts. Except for the root wood extract, strong repellent activity was observed for the rest of the extracts (P